Domestic humanitarianism: the Mission France of Médecins Sans Frontières and Médecins du Monde - Tine Hanrieder; Claire Galesne (Third World Quarterly, 2021)
What are the boundaries of humanitarianism? This question is controversially debated among humanitarian practitioners and scholars, given ever-changing spaces and temporalities of human suffering. This paper explores an understudied site of this controversy: the domestic humanitarian engagement of Médecins Sans Frontières and Médecins du Monde, two NGOs widely regarded as epitomes of liberal international humanitarianism. Their Mission France started in the 1980s to support vulnerable populations in France through medical aid, socio-legal support, and political activism. It has provoked fierce internal opposition ever since, in the name of an inherited vision of humanitarianism as impartial emergency aid. Drawing on organisational documents, archival sources and key informant interviews, we analyse how these conflicts gave rise to an unstable settlement around the diagnostic function of Mission France: Leaders aimed to make the assistance function of Mission France secondary to the advocacy function of drawing attention to health inequity, thus avoiding any long-term substitution for state services. However, the political strategizing demanded by this approach clashed with local volunteer preferences for immediate aid and claims to political neutrality. This conflict about the hierarchy of humanitarian values in the NGOs' home country sheds new light on the contentious politics of humanitarian witnessing and assistance.
Keywords: 300; humanitarianism; health policy; international nongovernmental organisations; France; Médecins Sans Frontières; Médecins du Monde